Cost Analysis of M/M/1/N queue with working breakdowns and a two-phase services. Issue 1 (May 2021) - Vijayalakshmi, V.; Kalidass, K.; Deepa, B.
Abstract: In this article, we analyze the finite capacity Markovian queueing model with working breakdowns and a two-phase service. The server provides the primary service as well as the secondary elective service. The cost optimization problem is to find out the minimum cost per unit time by a direct search method to optimize service rates.